COGNITIVE PROTOTYPE AS A DATA STRUCTURE FOR COGNITIVE STRUCTURES STORING - O. A. Ryzhov; A. M. Popov (Medična Informatika ta Inženerìâ, 2016)
The analysis of formal models of knowledge representaion in human minds allowed us to forge a definition of two new concepts: cognitive prototype (CP) as a processable and flexible data structure for representing models of cognitive structures (CS) in computer environment and knowledge base (KB) of IES based on CPs as a UML-model to storage and further process the content of educational courses based on cognitive prototypes.